HUBUNGAN MODAL SOSIAL DENGAN PEMANFAATAN DAN KELESTARIAN HUTAN LINDUNG - Sulistya Ekawati; Dodik Ridho Nurrochmat (Centre for Research and Development on Social, Economy, Policy and Climate Change, 2014)
The concept of social capital and collective action began to receive attention in common pool resources management such as in the case of protected forest. Forms of social capital in this study were social leadership, custom/cultural/local knowledge, beliefs and social institutions. This study aimed to analyze the relationship between social capital, economic benefits and ecological benefits of protected forest. The study was conducted in three regencies, namely East Tanjung Jabung and Sarolangun (Jambi Province) and South Solok (West Sumatra Province). Data were collected through interviews, focus group discussions and field observations. Data analysis was performed with the program SPSS 17.0 Statistics to estimate the curve on the menu regression analysis. The result showed: the social capital (refer to actor perspective and public perspective) positively correlated with the sustainability of protected forest; the correlation of economic benefits received by forest communities and forest sustainability was negative; the ecological benefits positively correlated with forest sustainability.